Vegetation Succession on Drained Lakes in Old Crow Flats, 2007-2009 - Nagwan, Lance; Lantz, Trevor; Tizya, Erika (Canadian Cryospheric Information Network, 2011)
Temperature increases in northern ecosystems are altering the freqeuncy of natural disturbance. Increased disturbance is likely to exert a strong influence on terrestrial vegetation. In the Old Crow Flats in the Northern Yukon, we investigated the effect of catastrophic lake drainage on plant community composition, vegetation structure and microenvironment by contrasting drained lake basins of various ages with several undisturbed terrain types. The vegetation that develops on drained lakes basins is typically dominated by canopy forming willows. Plant community composition at these sites is significantly correlated with thaw depth, organic layer thickness, and moisture. Differences in species composition between disturbed and undisturbed sites indicate that plant communities developing on drained basins can remain distinct for approximately a century. Preliminary data analysis suggests that long-term succession may follow two principle trajectories, which likely depend on the environmental conditions following drainage. The persistence of distinct plant communities on drained lake basins suggests that an increase in the area affected by drainage will have a strong impact on both landscape heterogeneity and wildlife habitat. Additional work to characterize vegetation using fine-scale infrared photography will verify if the patterns observed in the field are also evident at the landscape scale. : Purpose: To describe changes in environment and plant community composition following lake drainage. : Summary: Not Applicable